Response to Growth and Production of Cherry Tomatoes to KNO3 and Pruning Treatments - M Abror (Nabatia, 2020)
The purpose of this study was to determine the interaction between KNO3 and pruning on the growth and production of cherry tomato plants. To determine the response between treatments on the growth and production of cherry tomato plants. The research was conducted in December 2017 - March 2018 using a randomized block design (RBD) with 2 factors and repeated 3 times. The first factor is KNO3, namely control, 2 gr, 4 gr and 6 gr, while the second factor is pruning and without trimming. The parameters observed were plant height, stem diameter, fruit weight per plant, number of fruits per plant, fruit weight per 20 fruit, plant wet weight, plant dry weight. The analysis used was analysis of variance and continued with the 1% and 5% BNJ test.